(untitled) - Elder, Janet (Boston, Mass., 2007)
Entryways into College Reading and Learning is a supportive, motivating introductory-level text for students who read at the fifth- to eighth-grade level and is designed to provide the foundation for success in subsequent developmental reading courses and, ultimately, their other college coursework. Its purpose is to strengthen their vocabulary-building and reading skills, as well as equip them with general learning strategies and study skills. Entryways offers a fresh approach for post high school students who have not adequately benefited from traditional instructional approaches in the past
Keywords: Reading (Higher education),Việc đọc (Giáo dục đại học)